Modeling and experimental evaluation of vibration reduction of hydraulic-driven joint with a MRF damper. (February 2023) - Meng, Xiangming; Zhang, Zhizhong; Sheng, Kaizhang; Yu, Chunmei; Huang, Hui; Chen, Shumei; Li, Yuzheng
In order to reduce the impact force of the legged hydraulic-robot when it is driving on the ground, a new method based on magnetorheological technology is proposed for damping control of hydraulic mechanical legs in this paper. Firstly, the structure of hydraulic-driven leg with magnetorheological fluid (MRF) damper is designed, and the magnetic field simulation analysis of MRF damper is carried out to verify the rationality of magnetic circuit. Then the effects of different damping ratios on the dynamic performance of valve-controlled cylinder system are analyzed by theoretical modeling. Further, the co-simulation modeling of MRF damper and valve-controlled cylinder is established based on AMESIM to analyze the vibration reduction effect under impact force. Finally, the experiments of the hydraulic system designed in this paper are carried out under step load and triangular-wave load to obtain the system output displacement and pressure under two kinds of loads. Compared with the results without MRF damper, it is found that the new method can reduce the increase of pressure impact by 82% and almost eliminate the pressure fluctuation in the high pressure chamber of hydraulic cylinder.